Economic and organizational impact of the changing hospital funding practices of erythropoiesis-stimulating agents on the management of care of dialysis patients in France. (14th March 2018) - Therasse, Carole; Fusier, Isabelle; Cordonnier, Anne-Laure; Bérard, Florence; de Curzon, Olivier Parent; Bocquet, François; Paubel, Pascal
Aim: Erythropoiesis-stimulating agents (ESAs) are particularly used to treat dialysis patients suffering from anemia due to renal failure. Since March 2014, ESAs have no longer been funded on top-of-diagnosis-related groups (DRGs) in French hospitals and are funded via DRGs. There are two ways to fund dialysis in French hospitals: the 'DRG for dialysis in session' and the 'off-dialysis DRG', which is not a DRG and consists in a supplement tariff specific to dialysis for patients hospitalized for another main reason than dialysis. The aim of this study is to assess the impact of this funding change on the dialysis activity and on the budget of the 37 University Public University Hospitals in Paris (10% of the hospitalizations in France).Materials & methods: A before–after study (March–September 2013 vs March–September 2014) was conducted. Medical activity data (and ESAs consumption data) were used to assess the number and costs of DRGs associated with ESAs use. As we do not have access to the whole dialysis activity over the period studied, two hypotheses were considered: the proportion of the dialysis activity was constant between the two periods (Hypothesis A); the dialysis activity was correlated to ESA consumptions delivered by hospital pharmacies to healthcare units (Hypothesis B). A budget impact analysis was also conducted taking into account the evolution of DRG costs and ESA prices.Results: The number of dialysis 'DRG for dialysis in session' with ESA consumption have increased by 5% (Hypothesis A) and decreased by 9% (Hypothesis B) between the two periods while the volume of 'off-dialysis DRG' with ESA consumption increased by 2% (Hypothesis A) and by 9% (Hypothesis B). The budget impact was -€1.02 million (Hypothesis A) and -€0.7 million (Hypothesis B) leading to a loss for our hospitals.Conclusion: There is no significant impact of the change of funding of ESAs on the hospital activity. The DRG-based payment is negative for the budget of our hospitals but is positive for the French National Health Insurance. Indeed, with the price decrease, the ESAs are more costly for hospitals (not funded on top-of-DRG), but less costly for the society.